Sarcoidosis and Adrenal Angiomyolipoma – a rare tumor and a rarer coincidence - Selviambigapathy, Jayakumar; Kamalanathan, Sadishkumar; Sahoo, Jayaprakash; Barwad, Adarsh Wamanrao; Ramkumar, Govindarajalou; Vivekanandan, Muthupillai; Srinivas, B.H.; Jacob, Sajini Elizabeth; Manikandan, R (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Angiomyolipoma is a benign mesenchymal tumor occurring in about 0.3 % of the general population. Angiomyolipoma of the adrenal gland is a rare entity, and only 5 cases have been reported so far in English literature. Sarcoidosis is a systemic illness of unknown etiology characterized histologically by non-caseating epithelioid granulomas in the affected tissues. Angiomyolipoma of the adrenal occurring in sarcoidosis is an unusual association with no prior published reports. We describe a case of adrenal angiomyolipoma in a 60 year old female with sarcoidosis.